El estatuto del ser humano en estado embrionario en el proyecto del Código Civil - Herrera, Daniel Alejandro (2012)
Fil: Herrera, Daniel Alejandro. Pontificia Universidad Católica Argentina. Facultad de Derecho; Argentina